Common milk adulterants in developing country Nepal: A mini- review - Swotantra Dangi (Syiah Kuala University, 2021)
Milk adulteration is a serious concern in developing country Nepal and is at higher risk due to lack of government policies. Milk is almost a complete food containing essential nutrients required for growth and maintenance of the body. Milk is a high-risk commodity that can be adulterated in numerous ways and turn affects milk quality. The quality and safe milk production are one of the biggest problems faced by developing countries, and Nepal is one of them. The reason behind the milk adulteration is more for economic concerns, but the root cause of adulteration is to increase milk demand during the lean season in developing countries and the existing supply chain. Water being cheap is the most common adulterant added in the milk that decreases the nutrient content of milk. Milk producer also adds the preservatives to increase the shelf life of milk, caustic soda to reduce the milk acidity and materials like urea, starch, sugar and milk powder to increase SNF content. Such milk adulterants can possess serious health hazards to the public leading to fatal diseases. This review shows the common milk adulteration practices in-country Nepal and their impacts on food safety and human health and emphasize potential strategies for control of such adulteration practices.Keywords:Adulteration, Milk quality, food safety, human healthself Adam, A.A.H. 2009. Milk adulteration by adding water and starch at Khartoum state. Pakistan Journal of Nutrition, 8(4):439-440.Barham, G.S., Khaskheli, M. Soomro, A.H. and Nizamani, Z.A. 2014. Extent of extraneous water and detection of various adulterants in market milk at Mirpurkhas, Pakistan. J Agri Vet Sci, 7(3), pp.83-89.Barham, G.S., Khaskheli, M., Soomro, A.H. and Nizamani, Z.A.2014b. Detection and extent of extraneous water and adulteration in milk consumed at Hyderabad, Pakistan. In Food Nutrition Sciences ,2: 47-52.Bastola, K.P., Nepali, D.B. 2016. Quality of Raw Milk Supplied to Organized Milk Collection Centers of Western Chitwan. International Journal of Thesis Projects and Dissertations (IJTPD),4 (1): 1-19.Borin, A., Ferrao, M.F. Mello, C. Maretto, D.A. Poppi, R.J. 2006. Least-squares support vector machines and near infrared spectroscopy for quantification of common adulterants in powdered milk. Analytica chimica acta, 579(1): 25-32.CBS, N.2011. Statistical year book of Nepal. Central Bureau of Statistics.Chaudhary, B., Upadhyaya, M. 2013. Socio-economic impacts of dairy cooperative. Economic Journal of Development Issues, 15-23.Cheng, Y., Dong, Y. Wu, J. Yang, X. Bai, H. Zheng, H. Ren, D. Zou, Y. Li, M. 2010. Screening melamine adulterant in milk powder with laser Raman spectrometry. Journal of Food Composition and Analysis, 23(2):199-202.Dahal, L.R., Karki, D.B.N. Shah, R.2010. Total bacterial counts of raw milk in Eastern Terai of Nepal. Journal of Agriculture and Environment, 11:46-50.Dai, X., Zhao, Y. Li, M. Fang, X. Li, X. Li, H. Xu, B. 2012. Determination of urea in milk by liquid chromatography-isotope dilution mass spectrometry. Analytical letters, 45(12):1557-1565.Desissa, F., Makita, K. Teklu, A. Grace, D. 2012. Contamination of informally marketed bovine milk with Staphylococcus aureus in urban and peri urban areas of Debre-Zeit, Ethiopia. African Journal of Microbiology Research, 6(29): 5852-5856.Executive Summary on National Survey on Milk Adulteration .2011. Food safety and standards authority of India.www.fssai.gov.in/Portals/0/Pdf/sample_analysed (02-01-2012).pdf. Accessed on January7 2021.FAO., 2010. Dairy Sector Study of Nepal. Food and Agriculture Organization of the United Nations (FAO).Faraz, A., Lateef, M. Mustafa, M.I. Akhtar, P. Yaqoob, M. Rehman, S. 2013. Detection of adulteration, chemical composition and hygienic status of milk supplied to various canteens of educational institutes and public places in Faisalabad. JAPS, Journal of Animal and Plant Sciences, 23(1 Supplement), 119-124.Fischer, W.J., Schilter, B. Tritscher, A.M. Stadler, R.H.2011. Contaminants of milk and dairy products: contamination resulting from farm and dairy practices. Encyclopedia of Dairy Sciences, 2: 887-97.Gale Jr, H.F. Hu, D. 2009. Supply chain issues in China’s milk adulteration incident (No. 1005-2016-79204).Gossner, C.M.E., Schlundt, J. Ben Embarek, P. Hird, S. Lo-Fo-Wong, D. Beltran, J.J.O. Teoh, K.N. Tritscher, A. 2009. The melamine incident: implications for international food and feed safety. Environmental health perspectives, 117(12):1803-1808.Handford, C.E., Campbell, K. Elliott, C.T. 2016. Impacts of milk fraud on food safety and nutrition with special emphasis on developing countries. Comprehensive Reviews in Food Science and Food Safety, 15(1):130-142.Ingelfinger, J.R.2008. Melamine and the global implications of food contamination. New England Journal of Medicine, 359(26):.2745-2748.Kamthania, M., Saxena, J. Saxena, K. and Sharma, D.K. 2014. Methods of Detection Remedial Measures. Int J Engg Tech Res, 1:15– 20.Kandpal, S.D., Srivastava, A.K. Negi, K.S. 2012. Estimation of quality of raw milk (open branded) by milk adulteration testing kit. Indian journal of community health, 24(3):188-192.Khalid, A.2006. Milk production in Sudan (conference) Kh Sudan: 1-3.Khan, B.B., Mustafa, M.I. Abdullah, M. Yaqoob, M. 1991. Chemical and hygienic quality of milk supplied to canteens of various hospitals in Faisalabad city. Pak. J. Agri. Sci, 28(4):404-7.Khan, K.M., Krishna, H. Majumder, S.K. Gupta, P.K. 2015. Detection of urea adulteration in milk using near-infrared Raman spectroscopy. Food analytical methods, 8(1):93-102.Kumar, A., Thapa, G. Joshi, P.K. Roy, D. 2016. Adoption of food safety measures among Nepalese milk producers: Do smallholders' benefit? (Vol. 1556), Intl Food Policy Res Inst.Lateef, M., Faraz, A. Mustafa, M.I. Akhtar, P. Bashir, M.K. 2009. Detection of adulterants and chemical composition of milk supplied to canteens of various hospitals in Faisalabad city. Pakistan Journal of Zoology, 9:139-142.Lin, M., He, L. Awika, J.Yang, L. Ledoux, D.R. Li, H.A. Mustapha, A. 2008. Detection of melamine in gluten, chicken feed, and processed foods using surface enhanced Raman spectroscopy and HPLC. Journal of food science, 73(8): T129-T134.Liu, Y., Todd, EED. Zhang, Q. Shi, JR. Liu XJ.2012. Recent developments in the detection of melamine. J Zhejiang Univ Sci B (Biomed Biotechnol),13(7): 525–32.Lues, J.F.R., Venter, P. Van der Westhuizen, H. 2003. Enumeration of potential microbiological hazards in milk from a marginal urban settlement in central South Africa. Food Microbiology, 20(3): 321-326.Mu, L., Dawande, M. Mookerjee, V. 2014. Improving the milk supply chain in developing countries: Analysis, insights, and recommendations. Production and Operations Management, 23(7): 1098-1112.NDDB.2014. Final Report on Study on Cost of Milk Production. Hariharbhawan, Lalitpur, IndiaNDDB/C/RFP/2072-73/01. Final Report on “Benchmark Survey on Quality of Raw and Processed Milk in Nepal